Assessing patient-reported outcomes in asthma and COPD patients: which can be recommended in clinical practice?. Issue 1 (January 2018) - Kocks, Janwillem W.H.; Seys, Sven F.; van Duin, Titia S.; Diamant, Zuzana; Tsiligianni, Ioanna G.
Abstract : Purpose of review: There is a clear need for simple and reliable patient-reported outcome measures for chronic obstructive pulmonary disease (COPD) and asthma in daily practice. The purpose of this review is to facilitate the choice for clinicians of patient-reported outcomes which they can use in their daily practice. Recent findings: More than 50 patient-reported outcome measures for asthma and COPD exist and clinicians are often left confused on which to use. Four tools (two for asthma and two for COPD) can be suggested based on validity/reliability, responsiveness, practicality and are particularly convenient in terms of time to measure. Summary: On the basis of ample evidence, the COPD assessment test and the clinical COPD questionnaire for COPD and asthma control questionnaire and the asthma control test for asthma can be recommended for use in both primary care and other clinical settings. A simple guide figured as smiley faces has been designed to assist physicians to easily select the appropriate measure. With the current direction of thinking into treatable traits, targeted measures that evaluate the upper airways like the control of allergic rhinitis and asthma test may also be more used in the future. Abstract : Supplemental Digital Content is available in the text